Sir John Franklin and the Arctic regions [electronic resource] : a narrative, showing the progress of British enterprise for the discovery of the North-West Passage during the nineteenth century : with detailed notices of the expeditions in search of the missing vessels under Captain Sir John Franklin - Simmonds, P. L. (Peter Lund), 1814-1897. (London : G. Routledge, 1851)
Tables. Includes publisher's advertisements. '"Miserable they/Who here entangled ."--Cowper.' Electronic reproduction. Mode of access: Internet. 44